An Important Role of Educational Supervision in the Digital Age - Ismail, Izwah binti (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
Educational supervision is one of the most important supports for the educational system and educator’s professional development. This paper attempts to highlight the importance role of educational supervisor in digital age. There are three significance factors for efficient educational supervision in the higher educational institution which are Teaching & Learning,Digital Ethics and Training and Professional Development. Education is no longer restricted to considering human needs and the requirements of thepresent, but it seeks to address and reflect on developing human skills and capacities, and thenecessities of the future. Digital age demand the educatorsto undertake life-long, upgrading, reviewing of their ownprofessional learning and adopting continuous professional development. In order to help students to gainaccess to information independentlyand practice the digital ethics, educator in digital age needs a new approaches to teach includingthose that emphasize high order thinking skills, constructivists approaches tolearning and understanding, co-operative learning strategies, multipleintelligence, and the use of computer-based and other technology related. At this stage, the most suitable training for the right person at the right time is required and a Training Need Analysis (TNA) is crucially necessary. CUDBAS is one of the approaches for TNA to structure the training need. The quality ofeducation cannot be improved by only adding more resources into the system. It also calls foreffective management of these resources at the school level, ensuring an effective system ofprofessional supervision, and preventing the deterioration of essential support structures foreducators. Through quality collaboration, educators could move from their subjectivity anddraw some conclusions about their experiences and views. This makes educationalsupervision, which is a co-operative problem-solving process a crucial concept in theprofessional development of educators.